A Demonstration of compilability for UML template instances - Farinha, José (2016)
Because of the thin set of well-formedness rules associated to Templates in UML, ill-formed elements may result from well-formed bindings to templates. Although such ill-formedness is generally detected by some UML validation rule, the problem is poorly reported if the violated rule does not pertain to the Template construct. Typically, erroneous substitutions of template parameters will be misleadingly reported as compilation problems in the code of operations of the template’s instance. This paper demonstrates that a set of well-formedness rules, additional to those of the standard UML, prevents this problem from occurring. Such set of constraints was proposed in a previous paper and named Functional Conformance (FC), but a demonstration of its effectiveness was not provided. Such a demonstration is carried out in the current paper adopting UML Activities as the formalism to represent the dynamics of systems and their well-formedness rules as compilability criteria. Carrying out the demonstration revealed further rules than those previously proposed for FC.